2016
DOI: 10.1038/srep27762
|View full text |Cite
|
Sign up to set email alerts
|

Association of androgen with gender difference in serum adipocyte fatty acid binding protein levels

Abstract: Clinical investigations have indicated women have higher levels of adipocyte fatty acid binding protein (A-FABP) than men. The present study aimed to identify factors related to gender difference in serum A-FABP levels. A total of 507 participants (194 men, 132 premenopausal women, and 181 postmenopausal women) were enrolled in the present study. Serum A-FABP levels increased in the order from men to premenopausal women to postmenopausal women in both body mass index categories (<25.0 and ≥25.0 kg/m2; all P < … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 33 publications
1
14
1
1
Order By: Relevance
“…Furthermore, the effects of testosterone vary with the different active forms related to sex hormone-binding globulin between premenopausal women and postmenopausal women. 17 Consistent with these findings, the present study confirmed that the serum A-FABP levels increased in the order from men to premenopausal women to postmenopausal women, suggesting that the gender- and menopause-related differences in serum A-FABP levels should be taken into consideration when A-FABP was used as a serum biomarker.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, the effects of testosterone vary with the different active forms related to sex hormone-binding globulin between premenopausal women and postmenopausal women. 17 Consistent with these findings, the present study confirmed that the serum A-FABP levels increased in the order from men to premenopausal women to postmenopausal women, suggesting that the gender- and menopause-related differences in serum A-FABP levels should be taken into consideration when A-FABP was used as a serum biomarker.…”
Section: Discussionsupporting
confidence: 90%
“…4 Owing to gender differences in serum A-FABP levels observed in our previous study, 17 the present study divided the study population into subgroups of men, premenopausal women and postmenopausal women for analysis.…”
Section: Methodsmentioning
confidence: 96%
“…FABP4 level is significantly higher in females than in males, possibly due to the larger amount of body fat in females than in males since there is an independent and strong correlation between FABP4 level and adiposity 70, 71) . In addition, androgen may partially contribute to the gender difference in serum FABP4 levels 72) . Circulating FABP4 levels are significantly correlated with norepinephrine levels during exercise testing 73) , being consistent with FABP4 secretion from adipocytes via β -adrenergic-mediated lipolytic mechanisms 5456) .…”
Section: Circulating Fabp4 Levelmentioning
confidence: 99%
“…Greater age and female gender were both also associated with higher baseline FABP4. Factors accounting for gender differences include androgen hormone production and body composition 44 .…”
Section: Discussionmentioning
confidence: 99%